Penerapan Lembar Kerja Murid Lingkubaca Upaya Peningkatan Sikap Komunikasi dan Pemahaman Membaca Murid SD Kelas I - Apriliana, Karina Yossi; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Although the Talking Stick instructional model has been widely studied, research that specifically integrates the Lingkubaca Student Worksheet (Lembar Kerja Murid [LKM] “Lingkubaca”) with concrete media based on contextual images to enhance beginning reading skills and communication attitudes in Grade I students remains very limited. This study aims to describe the implementation of Talking Stick supported by the Lingkubaca Student Worksheet and to test its effectiveness in improving students’ ability to read simple words and sentences as well as their communication attitudes. The study employs a mixed-methods approach with a one-group pretest–posttest design, involving 10 students selected through purposive sampling. Data were collected through observation, interviews, documentation, and worksheet-based tests, and analyzed using descriptive quantitative and qualitative methods. The findings show a significant improvement in beginning reading skills, with the average score increasing from 58.50 to 81.70, accompanied by positive developments in communication attitudes. These results reinforce cognitive development theory that emphasizes the importance of concrete media and social interaction in learning among students at the concrete operational stage and extend understanding of the effectiveness of game-based learning in early literacy development. The study concludes that the collaboration of reading activities, educational games, and oral communication is a key strategy for building basic literacy in early-grade students and provides theoretical implications for early literacy studies as well as practical guidance for teachers seeking to optimize the use of concrete media and thematic worksheets in enhancing the literacy of Phase A (fase A) students.